A conceptual digital transformation design for International Islamic University Malaysia to ‘University of the Future’ - Zahari, Nurul Auni; Mustapa, Malina; Ibrahim, Jamaludin; Qayyum Nasser, Siti Shyahirah; Ahmad Dahlan, Abdul Rahman (IEEE, 2018)
Higher education sector in Malaysia continues to face changes and pressure on the digital capabilities, socioeconomy technology, industry trends, financial support and universal standard that demand institutional change if success is to be sustained and determined over the long term. International Islamic University Malaysia as one of the public university should grow and thrive towards long term planning for a future that will look very different from their past. The university should undergone significant changes on their strategic plans to achieve excellence academic performance and top academic rankings locally and globally. Thus, this paper identifies the main drivers and megatrends effecting the university along with the opportunities, challenges and implications towards the model of university of the future. It also provides some game changers and key projects for the university to implement for transformation in the future.